Electrochemical behaviour of substances responsible for the vanilla aroma and a study of their structural analogues at the glassy carbon electrode - Farag, Amir Shaaban; Švancara, Ivan; Sýs, Milan (University of Pardubice, 2020)
In this article, the electrochemical behaviour of vanillin, ethylvanilin, and of their structural analogues has been studied at the glassy carbon electrode using cyclic voltammetry. Based on experimental observations and information from literature, the respective electrode reaction pathways were proposed according to the ECE mechanisms in all cases, when up to three oxidation products were identified from one reactant. It has been found that the electrode oxidation of vanillin and ethylvanillin occurs in one single step, followed by hydrolysis in ortho-position and/or cleavage of the corresponding alcohol, giving rise to two electrochemically reversible oxidation products.
Elektrochemické chování látek zodpovědných za vanilkové aroma a studium jejich strukturních analogů na elektrodě ze skelného uhlíku
Keywords: vanillin; ethylvanillin; o-Cresol; guaiacol; 4-Hydroxybenzaldehyde; Vanilin; ethylvanilin; o-kresol; guajakol; 4-hydroxybenzaldehyd